STUDY OF AL-SUBSTITUTED HEMATITES, PREPARED FROM THERMAL TREATMENT OF LEPIDOCROCITE - Van San E.; De Grave E.; Vandenberghe R.E.; Desseyn H.O.; Barrón V.; Datas L.; Rousset A. (My University, 2001)
A study of the characteristics of the Morin transition in aluminous hematites, α-(Fe1−xAlx)2O3, produced from thermally transformed lepidocrocites, is reported. Six compositions with Al contents between 0.2 and 10 at% have been considered. It is argued that these samples present the advantage that they contain smaller amounts of hydroxyl and water as compared to hematites obtained by other preparation methods. The samples were characterised by a variety of conventional techniques, including thermal analyses, X-ray diffraction, FTIR, TEM/EDX, BET surface-area measurements and diffuse reflectance spectroscopy. All results indicate that the Al is structurally incorporated in the hematite lattices. Transmission Mössbauer spectra were recorded at various temperatures between 80 K and room temperature in order to precisely determine the Morin-transition region and the spin structure in both the low-temperature antiferromagnetic and weakly ferromagnetic states. It was found that the Morin-transition temperatures are markedly higher as compared to similar hematites made from aluminous goethites and that a transition phenomenon persists to an Al substitution of up to at least 10 at%. This different behaviour is ascribed to lower concentrations of structural hydroxyl groups in these lepidocrocite-based hematites.